Sanctum of the Bhairon shrine at the Harsha hill - Temples of India Project Team (Jio Institute, 2024)
Close to the Harshnath temple complex lies the Bhairon shrine, with a semi-iconic rock, locally known as the Harsha Bhairon. He is believed to be a manifestation of the folk hero, Harsha, who decided to settle at the hill to worship Shiva and was blessed by the latter to be worshipped at the hill as Bhairon. Several 10th-century CE sculptures are fixed on the walls of this complex. Today, the Bhairon shrine is the epicentre of pilgrimage to Harsha Hill and is regarded as the family deity of several local castes.